Lifestyle changes in rural communities through spatial reproduction practices: A case study in Madiun Regency - Salsabila Damayanti; Nadia Egalita (Jurnal Sosiologi Dialektika, 2023)
The production of space in rural areas as a result of modernization changes lifestyles not only within families but also at a broader level, namely between communities. This study aimed to examine how spatial reproduction occurs in villages in Madiun Regency by identifying the dominant agent and the stages of the process of spatial reproduction. This study employed qualitative methods. This study found that there are four stages in the spatial reproduction process in Madiun Regency, including outreach, coordination, mutual cooperation, and synergy. These four stages occurred because of the presence of the village head as the initiating agent and Village Owned Enterprises (BUMDes) and the Tourism Awareness Group as organizations that oversee various community activities in the tourism sector. According to the findings of this study, technology has accelerated the process of spatial reproduction, which is reflected in the existence of four regionalizations, including economic, social, housing, and public services. This study concludes that the reproduction of space does not always lead to conflict and social inequality in society. On the contrary, people are able to work together in building shared prosperity with the value of mutual cooperation.